Comparative three-dimensional finite element analysis of implant-supported fixed complete arch mandibular prostheses in two materials - João Paulo Mendes Tribst; Dayana Campanelli de Morais; Alexandre Abhdala Alonso; Amanda Maria de Oliveira Dal Piva; Alexandre Luis Souto Borges (Wolters Kluwer Medknow Publications, 2017)
Background: The increase of requests for implant-supported prosthesis (ISP) with zirconia as infrastructure has attracted a lot of attention due to its esthetics, biocompatibility, and survival rate similar to metallic infrastructure. The aim of this study was to evaluate the influence of two different framework materials on stress distribution over a bone tissue-simulating material. Materials and Methods: Two ISP were modeled and divided into two infrastructure materials: titanium (Ti) and zirconia. Then, these bars were attached to a modeled jaw with polyurethane properties to simulate bone tissue. An axial load of 200 N was applied on a standardized area for both systems. Maximum principal stress (MPS) on solids and microstrain (MS) generated through the jaw were analyzed by finite element analysis. Results: According to MS, both models showed strains on peri-implant region of the penultimate (same side of the load application) and central implants. For MPS, more stress concentration was slightly higher in the left posterior region for Ti's bar. In prosthetic fixation screws, the MPS prevailed strongly in Ti protocol, while for zirconia's bar, the cervical of the penultimate implant was the one that highlighted larger areas of possible damages. Conclusions: The stress generated in all constituents of the system was not significantly influenced by the framework's material. This allows suggesting that in cases without components, the use of a framework in zirconia has biomechanical behavior similar to that of a Ti bar.